ZONING OF EXHAUST GRAVITATIONAL VENTILATION SYSTEMS IN RESIDENTIAL BUILDINGS - Kaminat M. Agakhanova (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Abstract. Objectives The article is devoted to an analysis of the systems of supply and exhaust ventilation in mass-constructed residential buildings with the purpose of justifying the need for separation of gravitational exhaust ventilation systems into zones on the example of a nineteen-storey residential building. Methods  The need for zoning of the ventilation system is determined by the traditional aerodynamic calculation, which in this article is carried out using universal programmes compiled in computational systems such as Excel and Mathcad. Results An aerodynamic calculation of the natural ventilation system of the selected object is carried out for several options: the ventilation scheme actually designed in this building (separation of the exhaust gravitational ventilation system into two prefabricated vertical channels with individual satellites connected to it) and the traditional scheme of natural ventilation (identical scheme, but with a single prefabricated vertical channel). Analysis of the results does not give an unambiguous answer concerning the need for zoning of exhaust systems. For an accurate determination of the necessity of zoning the ventilation system, aerodynamic calculations were carried out for 40 and 60-storey buildingshaving the same layout. In the aerodynamic calculation, pressure losses of the system sections were determined as the sum of pressure losses due to friction and in local resistances. The obtained values had to correspond to the required discrepancy. The difficulty is in the determination of the coefficients of local resistances (CLR) of triple junctions due to the wide variety of calculation formulas and tabulated values. Conclusion The analysis of the results of the aerodynamic calculation of the selected natural ventilation systems determines the need for zoning the exhaust systems along the building's vertical aspect.